Lecture of Varlam Cherkhezishvili on the Necessity of Georgia’s Entry into the League of Nations - Matsaberidze, Malkhaz (Politics / პოლიტიკა, 2023)
In March, 1920, upon his return from the Western Europe, Varlam Cherkhezishvili delivered a cycle of lectures in Tbilisi on the League of Nations, which commenced on January 16, 1920. Varlam Cherkhezishvili stressed the importance of the League of Nations in the process of disarmament, imposing peace in the World and in the protection of the rights of workers; he particularly pointed out the common spirit of the socialist parties towards this organization. By that time, Georgia was not de jure recognized yet, thus Cherkhezishvili considered it as an absolute necessity to make the activities of the Society of the League of Nations more widespread in Georgia. This would pave the way for Georgia’s eventual membership into the League of Nations.  Key words: Georgia, League of Nations, Varlam Cherkhezishvili.